The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1186/s12870-014-0330-3
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization of candidate genes in QTL regions based on associations between traits and biological processes

Abstract: BackgroundElucidation of genotype-to-phenotype relationships is a major challenge in biology. In plants, it is the basis for molecular breeding. Quantitative Trait Locus (QTL) mapping enables to link variation at the trait level to variation at the genomic level. However, QTL regions typically contain tens to hundreds of genes. In order to prioritize such candidate genes, we show that we can identify potentially causal genes for a trait based on overrepresentation of biological processes (gene functions) for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 81 publications
(69 reference statements)
1
37
0
Order By: Relevance
“…The results are shown in Supplementary Table S2. To avoid overly broad functional categories, we marked those GO terms higher than 1% within the genome in gray (Bargsten et al, 2014) and excluded them from further analyses (Supplementary Table S2). We found that the most significantly enriched GO biological process (FDR = 8.29E-09) in cluster 5 was fatty acid biosynthetic process ( Figure 2B ; Supplementary Table S2), which has a temporal expression pattern of “up-down-down” ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The results are shown in Supplementary Table S2. To avoid overly broad functional categories, we marked those GO terms higher than 1% within the genome in gray (Bargsten et al, 2014) and excluded them from further analyses (Supplementary Table S2). We found that the most significantly enriched GO biological process (FDR = 8.29E-09) in cluster 5 was fatty acid biosynthetic process ( Figure 2B ; Supplementary Table S2), which has a temporal expression pattern of “up-down-down” ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Several causal variant or gene prioritization methods have been developed for human data but 223 not many in plants (Bargsten et al, 2014;Jagadeesh et al, 2016;Kircher et al, 2014;Schaefer et 224 al., 2018). Most prioritization methods have been developed for GWAS mapping in human, an 225 organism where linkage mapping cannot be performed.…”
Section: A Machine-learning Algorithm To Prioritize Qtl Causal Genes 222mentioning
confidence: 99%
“…A causal gene prioritization is especially helpful for the large QTLs identified by 228 linkage mapping, which can constitute hundreds to thousands of genes. One method has been 229 developed in rice to prioritize causal genes for linkage mapping (Bargsten et al, 2014). This 230 method is based on the hypothesis that causal genes from multiple QTLs of the same trait are 231 more likely to have the same biological process GO terms, and therefore genes with 232 overrepresented biological process GOs were prioritized as causal genes.…”
Section: A Machine-learning Algorithm To Prioritize Qtl Causal Genes 222mentioning
confidence: 99%
See 2 more Smart Citations